Coaching and coach development in New Zealand - Kidman, L.; Keelty, D. (International Sport Coaching Journal, 2015)
The purpose of this article is to provide an overview of coaching and coach development in New Zealand. For a small country with a population of 4.47 million (Statistics New Zealand, 2015), New Zealand achieves great success on the world sporting stage. One of the many contributors to this success is New Zealand`s commitment to developing coaches with an emphasis on continuous improvement through the provision of ongoing learning opportunities for coaches (SPARC, 2006). Interestingly the International Sport Coaching Framework`s recommendations aligns itself to such an emphasis that they refer to as lifelong learning (ICCE, 2013). To achieve this focus, and based on a Ministerial Taskforce findings that, "Coaching is in urgent need of support and development" (Ministerial Taskforce, 2001, p.10) Sport and Recreation New Zealand (SPARC) established a consultancy group to review and redevelop coaching. An outcome of this consultation was the production of the New Zealand Coaching Strategy (SPARC, 2004). Based on robust discussion on many issues of how people learn and coaching development philosophies, the Coach Development Framework (CDF) was established in 2006. Since its establishment, the CDF has been guiding coach development in New Zealand, placing the responsibility for this development on the National Sporting Organisations (NSOs).